2018
DOI: 10.1111/eje.12366
|View full text |Cite
|
Sign up to set email alerts
|

Oral Medicine for undergraduate dental students in the United Kingdom and Ireland—A curriculum

Abstract: This curriculum will act as a foundation for an increasingly shared approach between centres with respect to the outcomes to be achieved in Oral Medicine. The curriculum may also be of interest to others, such as those responsible for the training of dental hygienists and dental therapists. It provides a platform for future collective developments with the overarching goal of raising the quality of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Piboonniyom et al, also noted that clinical images enhance education as well as research. Mighell et al 2018 discussed oral medicine and management of oral mucosa pathology in the undergraduate curriculum and recommended case‐based discussion with pertinent images may help with learning and clinical decision‐making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piboonniyom et al, also noted that clinical images enhance education as well as research. Mighell et al 2018 discussed oral medicine and management of oral mucosa pathology in the undergraduate curriculum and recommended case‐based discussion with pertinent images may help with learning and clinical decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a consensus undergraduate curriculum in Oral Medicine in the United Kingdom (UK) and Republic of Ireland, presented the importance of teaching management of mucosal pathologies as a part of oral health care. The authors suggested including clinical images in the teaching process.…”
Section: Introductionmentioning
confidence: 99%
“…The oral mucosa has a limited repertoire of responses to disease, and a broad spectrum of diagnoses may present as lumps, ulcers, and red or white patches. [10][11] An analysis of 44 007 oral biopsies submitted to an oral pathology service in the UK over a 30-year period presented 393 different diagnoses. Admittedly, the 20 most frequent diagnoses represented 32 616 biopsies, almost 75% of the overall total.…”
Section: The Spectrum Of Oral Diagnoses and The Diagnostic Dilemma Posed In Primary Carementioning
confidence: 99%
“…This curriculum sets a training standard that must be met for dental graduates to be successfully admitted to the Dental Register in the UK. 11 It is worth noting that in the analysis of 44 007 biopsies, in accordance with the stated training standard, dentists should be able to recognise the majority of…”
Section: The Spectrum Of Oral Diagnoses and The Diagnostic Dilemma Posed In Primary Carementioning
confidence: 99%
See 1 more Smart Citation